Treatment of squamous cell carcinoma of the anal canal: A new strategies with anti-EGFR therapy and immunotherapy. (March 2018) - Casadei Gardini, A.; Passardi, A.; Fornaro, L.; Rosetti, P.; Valgiusti, M.; Ruscelli, S.; Monti, M.; Casadei, C.; Pagan, F.; Frassineti, G.L.
Abstract: The incidence of squamous cell carcinoma of the anal canal (SCAC) is increasing in both sexes but the standard treatment remains that of 20 years ago. However, interesting data have recently emerged on the use of anti-epidermal growth factor receptor (EGFR) agents and immunotherapy in advanced disease. Thus, new avenues of research are opening up that will hopefully lead to more effective therapeutic strategies. We provide an overview of the latest studies published on this tumor and discuss the possible future therapeutic options for combination therapy, anti-EGFR treatment and radiotherapy.